A 22-amino-acid peptide regulates tight junctions through occludin and cell apoptosis - Zhu,Maoying; Lu,Juan; Shen,Jianyun; Fei,Lumin; Chen,Deyu (PeerJ, 2020)
Occludin is a structural protein of tight junctions (TJ) in the blood–testis barrier (BTB). A 22-amino-acid peptide (22AA) in the second extracellular loop can reversibly regulate TJ, but its regulatory mechanism is unknown. In this study, a 22AA-induced TJ destruction animal model was constructed to investigate the effect of 22AA on Sertoli cells (SCs) and spermatid counts and cell apoptosis at different time points using a multiplex immunofluorescence technique. The effect of 22AA on the location and distribution of occludin was analyzed via dual confocal fluorescence microscope. Western blotting was used to analyze dynamic changes in occludin expression. Real-time RT-PCR was used to analyze miR-122-5p expression changes. Sperm density counts and mating methods were used to analyze the effect of 22AA on fertility in mice. The results showed that 22AA promoted SC and spermatid apoptosis, downregulated occludin, upregulated miR-122-5p, and decreased sperm density and litter size before 27 days (27D). After 27D, the expression of occludin increased again, miR-122-5p expression decreased again, both sperm density and litter size returned to normal, apoptosis stopped, and spermatogenesis began to recover. Therefore, it can be concluded that 22AA can destroy TJ by downregulating occludin and inducing cell apoptosis. After 27D, TJ and spermatogenesis functions return to normal.
Keywords: Occludin; TJ; Apoptosis; Sertoli cell; Spermatid